The comparative characteristic of level of matrix metalloproteinase-9 and high-sensitive C-reactive protein indicators at comorbid course of arterial hypertension and chronic obstructive pulmonary disease - Yatsenko, Oleg (ScienceRise: Medical Science, 2017)
The pathogenetic connection between the hypertonic disease and the chronic obstructive pulmonary disease (COPL) is little studied. The aim of research is to study the level of matrix metalloproteinase-9 and high sensitive C-protein indicators at the hypertonic disease and the chronic obstructive pulmonary disease. Methods. There were examined 40 patients: 30 with the diagnosis of hypertonic disease of II stage, combined with the chronic obstructive pulmonary disease, and 10 patients with the chronic obstructive pulmonary disease. Matrix metalloproteinase-9 and high sensitive C-protein levels in blood plasma and also parameters of elastic properties of the pulmonary artery were determined in all patients. Results. At the data analysis it was established that indicators of matrix metalloproteinase-9 and high sensitive C-protein were higher at the comorbidity of the hypertonic disease and the chronic obstructive pulmonary disease comparing with the group of isolated chronic obstructive pulmonary diseases. The analysis of elastic properties of the pulmonary artery demonstrated the essential increase of its hardness at comorbid states comparing with chronic obstructive pulmonary diseases. Conclusions. In patients with the hypertonic disease and the chronic obstructive pulmonary disease matrix metalloproteinase-9 and high sensitive C-protein levels increase comparing with isolated chronic obstructive pulmonary diseases that may testify to the role of these markers in the injury of target organs of the cardiovascular system. The monitoring of the dynamic of chronic obstructive pulmonary disease development and system inflammation is possible at the expanse of the determination of matrix metalloproteinase-9 and high sensitive C-protein levels